The Clash of the Cultures - Bogle, John (Ascent Audio, 2019)
Over the course of his sixty-year career in the mutual fund industry, Vanguard Group founder John C. Bogle has witnessed a massive shift in the culture of the financial sector. The prudent, value-adding culture of long-term investment has been crowded out by an aggressive, value-destroying culture of short-term speculation. Mr. Bogle has not been merely an eye-witness to these changes, but one of the financial sector's most active participants. In The Clash of the Cultures, he urges a return to the common sense principles of long-term investing. Provocative and refreshingly candid, this book discusses Mr. Bogle's views on the changing culture in the mutual fund industry, how speculation has invaded our national retirement system, the failure of our institutional money managers to effectively participate in corporate governance, and the need for a federal standard of fiduciary duty. Mr. Bogle recounts the history of the index mutual fund, how he created it, and how exchange-traded index funds have altered its original concept of long-term investing. He also presents a first-hand history of Wellington Fund, a real-world case study on the success of investment and the failure of speculation. The book concludes with ten simple rules that will help investors meet their financial goals.